Android-based Library Application Development Case Study: Kalbis Institute Informatics Department - Lumba, Ester; Waworuntu, Alexander (I-STATEMENT, 2018)
Kalbis Institute has a library with a growing collection of books every year. Besides the main library, each department also has a mini library with a collection of books that are in line with the departments science. The Informatics Department is one of the departments at the Kalbis Institute which has a library, with an annual budget for purchasing books. The problem that often occurs is when the lecturers are assigned to buy books, sometimes the same book is purchased, while the department prioritizes book variations over the number of books. In addition, the position of the book when it is being borrowed is sometimes difficult to trace because the loan and book management system is still manual. This study produced an Android-based library application, which is expected to facilitate the management of the Kalbis Institute Informatics department. The search feature that can display titles, authors and book covers, is expected to help overcome the problem of buying the same books when lecturers want to buy books at bookstores. The development of this application adopts the Rational Unified Process (RUP) method.